Revision of the New Caledonian genus Pseudonthobium Paulian, 1984 (Coleoptera: Scarabaeidae: Epilissini) - Montreuil, Olivier; Théry, Thomas (Zootaxa, 2011)
A revision of the New Caledonian genus Pseudonthobium Paulian, 1984 is proposed, including the description of seven new species: P. doense new species, P. foveolatum new species, P. genieri new species, P. humboldtense new species, P. monteithianum new species, P. paniense new species, and P. sinuatotibiale new species. A key to the species, illustrations of parameres and male protibia, and a distribution map are provided for all species.